1989
DOI: 10.1016/0014-5793(89)81056-7
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide sequence of the maltotetraohydrolase gene from Pseudomonas saccharophila

Abstract: The nucleotide sequence of the Pseudomonas saccharophila gene encoding maltotetraohydrolase (G4-forming amylase) has been determined. The coding region for the G4-forming amylase precursor contained 1653 nucleotides. The deduced precursor protein included an N-terminal 21-residue putative signal peptide; the deduced mature form of G4-forming amylase contains 530 amino acid residues with a calculated molecular mass of 57 740 Da. Sequence similarities between the G4-forming amylase and other amylolytic enzymes o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 32 publications
(37 reference statements)
1
12
0
Order By: Relevance
“…The a-amylases of Pseudomonas stutzeri, Pseudomonas saccharophila and Pseudomonas sp. 7197 were all maltotetraose-forming enzymes (Fujita et al 1989;Zhou et al 1989). The Pseudomonas sp.…”
Section: Discussionmentioning
confidence: 99%
“…The a-amylases of Pseudomonas stutzeri, Pseudomonas saccharophila and Pseudomonas sp. 7197 were all maltotetraose-forming enzymes (Fujita et al 1989;Zhou et al 1989). The Pseudomonas sp.…”
Section: Discussionmentioning
confidence: 99%
“…Homology searches by protein blast indicated that AmyP (CAM98700) amino acid sequence showed 73% identities to glucan 1,4-alpha-maltotetraohydrolase precursor from Pseudomonas stutzeri A1501 (ABP81117) (Yan et al 2008), 72% to maltotetraose-forming amylase (AAA25707) from Pseudomonas stutzeri MO-19 (Fujita et al 1989), 72% to glucan 1,4-alpha-maltotetraohydrolase (CAA34708) from Pseudomonas saccharophila (Zhou et al 1989) and 67% to Glucan 1,4-alpha-maltotetraohydrolase (YP_00118 8621) from Pseudomonas mendocina ymp (unpublished). Four regions (I-IV) similar to G4-amylase which are conserved in a-amylases were also found in AmyP (Fig.…”
Section: Identification Of Strain 7193mentioning
confidence: 98%
“…So far various maltooligosaccharide-forming enzymes have been reported from Pseudomonas spp. That is, genes coding for G4-, and GS-forming amylases have been cloned (Fujita et al, 1989: Zhou et al,1989: Shida et al:. 1992.…”
Section: Starch Hydrolysis With Cloned Amylasementioning
confidence: 99%